2020
DOI: 10.3390/cancers12051236
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Response and Toxicity of Potential Pathways in Human Colon Cancer Cells Exposed to Titanium Dioxide Nanoparticles

Abstract: Titanium dioxide nanoparticles (TiO2-NPs) are widely used for biomedical and food applications, the toxicity of TiO2-NPs in vivo and in vitro has been elucidated, but the underlying cytotoxicity of TiO2-NPs against microRNA remains largely unknown. The purpose of this study was to analyze microRNA profiling induced by TiO2-NPs against NCM460 and HCT116 cell lines. Comparative analysis identified 34 and 24 microRNAs were significantly altered in the TiO2-NPs treated cells at concentrations of 3 μg/mL and 30 μg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
(119 reference statements)
0
7
0
Order By: Relevance
“…Therefore, their use as a food additive has been banned since the beginning of 2020 in France (USDA Foreign Agricultural Service, GAIN Report Number: FR1917). A recent study suggests that cellular uptake of TiO2 ENM induces dose-dependent oxidative stress and alterations in microRNA expression [ 29 ]. Our results support the idea that TiO2p ENM are not toxicologically inert and do induce changes in epigenetic regulation, via shared as well as unique mechanisms when compared to the other tested ENM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, their use as a food additive has been banned since the beginning of 2020 in France (USDA Foreign Agricultural Service, GAIN Report Number: FR1917). A recent study suggests that cellular uptake of TiO2 ENM induces dose-dependent oxidative stress and alterations in microRNA expression [ 29 ]. Our results support the idea that TiO2p ENM are not toxicologically inert and do induce changes in epigenetic regulation, via shared as well as unique mechanisms when compared to the other tested ENM.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 shows an overview of recent publications summarizing the effects of TiO 2 nanoparticles and E171 on various cell models along the oro-gastrointestinal route, as well as cell types found in organs, following the systemic distribution of these particles. Some studies on TiO 2 showed the ability to decrease cell viability and induce the formation of ROS, while others do not detect such effects [ 16 , 57 , 58 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ]. In some cases, the increase in ROS was accompanied by elevated oxidative stress levels and lipid peroxidation, which may lead to the induction of DNA damage and micronuclei [ 16 , 123 , 127 , 129 , 130 ].…”
Section: Health Effect Of Ingested E171mentioning
confidence: 99%
“…A mechanism of reactive oxygen species (ROS) induction has been frequently related to nanotoxicity [44]. In fact, a recent work showed an intracellular increase of reactive oxygen species (ROS) upon exposure of normal human colon cell lines (NCM460) and human colon cancer cells (HCT116) to TiO 2 , that was suggested as the cause of its cytotoxicity and was related to microRNAs 378b and 378 g expression [45]. Increased uptake of smaller TiO 2 might favor this type of mechanisms, explaining the results observed in HT29-MTX-E12 cells exposed to digested NM-105, and deserves further research.…”
Section: Cytotoxicitymentioning
confidence: 99%